Effects of Mechanical Compression on Chondrogenesis of Human Synovium-Derived Mesenchymal Stem Cells in Agarose Hydrogel - Ge, Yuxiang; Li, Yixuan; Wang, Zixu; Li, Lan; Teng, Huajian; Jiang, Qing (Frontiers in Bioengineering and Biotechnology, 2021)
Mechanical compression is a double-edged sword for cartilage remodeling and the effect of mechanical compression on chondrogenic differentiation still remains elusive to date. Herein, we investigate the effect of mechanical dynamic compression on the chondrogenic differentiation of human synovium-derived mesenchymal stem cells (SMSCs). To this aim, SMSCs encapsulated in agarose hydrogels were cultured in chondrogenic induced medium with or without dynamic compression. Dynamic compression was applied at either early time-point (day 1) or late time-point (day 21) during chondrogenic induction period. We found that dynamic compression initiated at early time-point downregulated the expression level of chondrocyte-specific markers as well as hypertrophy-specific markers compared with unloaded control. On the contrary, dynamic compression applied at late time-point not only enhanced levels of cartilage matrix gene expression, but also suppressed the hypertrophic development of SMSCs compared with unloaded controls. Taken together, our findings suggest that dynamic mechanical compression loading not only promotes chondrogenic differentiation of SMSCs, but also plays a vital role in the maintenance of cartilage phenotype, and our findings also provide an experimental guide for stem cell-based cartilage repair and regeneration.